Aromatase Inhibitor, Flax seed and Sage Effects on Adult Rats Fertility and Sexual Behavior - Heba jasem; Fadwa tawfeek (College of Education for Pure Sciences, 2020)
The current study was designed to detect estrogen role in adult  male rats by giving aromatase inhibitor ( ltrozole 1 mg̷  Kg. B. W) for 60 days orally to inhibit aromatase enzyme activity and to study the effect of giving source of estrogen flax seeds (25 g ̷ 100 g diet) and aqueous extract sage (1000mg ̷  Kg. B.W.) orally. The study showed that adult male rats treated with ltrozole resulted in a significant decrease in the weight of testes, prostate , percentage of live sperms , number of sperms , number of mounting , intromission, ejaculation and in the time period from mixing with females to the first mounting ,  intromission and ejaculation , the time period between mount and another, intromission and another, ejaculation and another, and significant increase  in the percentages of  dead as well as abnormal  sperms. Flax seeds treatment significantly reduced percentage of live sperms, number of sperms, number of  mounting , intromission, and ejaculation, and significantly increased percentage of dead sperms compared with control group. Sage extract treatment caused a significant decrease in number of sperms, number of mounting, intromission and ejaculation , as well as a significant increase in the time period from mixing of female to the first mounting,  first intromission and first ejaculation compared with control. The results showed that administration of sage extract with letrozole showed a significant increase in testis weight, percentages of live sperms and number of sperms, and asignificant decrease in dead and abnormal sperms compared with the letrozole group. Administration of flax seed with letrozole did not significantly change weight of the testis , prostate, percentage of live, dead , abnormal sperm and number of sperm compared with letrozole group. Administration of Flax seed and sage extracts to male rats treated with letrozole did not significantly change all the done tests of sex behavior. The study concluded that estrogen has an important role in the function of male reproductive system, which is shown through the negative effects of the aromatase inhibitor on the weights of the testis, prostate, live and dead and abnormal sperm, and sexual behavior. Sage extract, but not flax seed, has benefit effects on the defect induced by aromatase inhibitor letrozole  both flax seed and sage do not produce positive effects on sexual behavior .